Research note: the effect of strain amplitude produced by ultrasonic waves on its velocity - Nourifard, N.; Lebedev, Maxim (Wiley-Blackwell, 2018)
© 2018 European Association of Geoscientists & Engineers The effect of the amplitude of ultrasonic waves propagating through a sample is not often taken into account in laboratory experiments. However, ultrasonic waves can produce relatively large strain inside the sample, and thus change the properties of the sample. To investigate the effect of strain amplitude on the P-wave velocity, a series of ultrasonic wave propagation experiments were carried out on three different media. All measurements were performed at 1 MHz central frequency and at the strain levels inside propagating waves of ~3.0 × 10-6 to 6.0 × 10-5 without applying confining pressure to the sample. Strains in the waves were measured by a laser Doppler interferometer upon wave arrival on a free surface of the sample. The ultrasonic velocities were measured by a pair of P-wave transducers located at the same measuring point as the laser beam of the LDI. The effect of strain on P-wave velocity varied for different material. The P-wave velocity was calculated using both a first arrival and a first maximum peak at different applied voltage. The P-wave velocity remained unchanged for a pure elastic medium (aluminium); however, the velocity increased continuously with the increasing of the strain for polymethylmethacrylate and Gosford sandstone. For Gosford sandstone, velocity increases up to 0.8% with strain increase from 7.0 × 10-6 to 2.0 × 10-5. This effect of velocity increase with the strain induced by an ultrasonic wave can be explained by the in-elasticity of both the polymethylmethacrylate and Gosford sandstone samples.